Myelin-Associated Glycoprotein Gene and Brain Morphometry in Schizophrenia - Felsky, Daniel; Voineskos, Aristotle N.; Lerch, Jason P.; Nazeri, Arash; Shaikh, Sajid A.; Rajji, Tarek K.; Mulsant, Benoit H.; Kennedy, James (Frontiers in Psychiatry, 2012)
Myelin and oligodendrocyte disruption may be a core feature of schizophrenia pathophysiology. The purpose of the present study was to localize the effects of previously identified risk variants in the myelin associated glycoprotein gene on brain morphometry in schizophrenia patients and healthy controls. 45 schizophrenia patients and 47 matched healthy controls underwent clinical, structural magnetic resonance imaging, and genetics procedures. Gray and white matter cortical lobe volumes along with subcortical structure volumes were calculated from T1-weighted MRI scans. Each subject was also genotyped for the two disease-associated MAG single nucleotide polymorphisms (rs720308 and rs720309). Repeated measures general linear model analysis found significant region by genotype and region by diagnosis interactions for the effects of MAG risk variants on lobar gray matter volumes. No significant associations were found with lobar white matter volumes or subcortical structure volumes. Follow-up univariate general linear models found the AA genotype of rs720308 predisposed schizophrenia patients to left temporal and parietal gray matter volume deficits. These results suggest that the effects of the MAG gene on cortical gray matter volume in schizophrenia patients can be localized to temporal and parietal cortices. Our results support a role for MAG gene variation in brain morphometry in schizophrenia, align with other lines of evidence implicating MAG in schizophrenia, and provide genetically-based insight into the heterogeneity of brain imaging findings in this disorder.